Mineral content and physico-chemical parameters of honey from North regions of Algeria - Bella, Giuseppa Di; Licata, Patrizia; Potortì, Angela Giorgia; Crupi, Rosalia; Nava, Vincenzo; Qada, Benameur; Rando, Rossana; Bartolomeo, Giovanni; Dugo, Giacomo; Turco, Vincenzo Lo (Natural product research, 2022)
Honey is accepted as food and medicine by all generations both ancient and modern. In this study the concentrations of K, Mg, Na, Zn, Fe, Mn, Cu, Cr, Ni, Se, As, Pb, Cd, Sb, Ti, V, Co, Hg and the determination of some physico-chemical parameters in 29 multifloral honeys collected from different North regions of Algeria: Algiers, Bouria, Ghardaïa, Laghouat, M'sila, Naâma, Tlemcen and El Bayadth during year 2018 were carried out. All minerals were determined by ICP-OES/MS and Hg by DMA-80. The most abundant minerals decreased in the following order: K, Na, Mg, Fe, Zn. Lead content exceeded the Codex Alimentarius and the European Union in all honey samples analysed, Cd and As levels were lower than the limits fixed by the European legislation and the regulations of the Codex Alimentarius. The Recommended Dietary Allowance values and benchmark levels were employed to assess the honey quality and safety.